Perbandingan Tingkat Kesehatan Bank BUMN Dan BUMS Nasional Berdasarkan Metode RGEC Tahun 2017-2021 - Giga Azayaka Tatanka Putra; Ahmad Idris (STIKes Ibnu Sina Ajibarang, 2023)
Bank Indonesia issued regulations regarding the assessment of the health level of commercial banks based on PBI No.13/1/PBI/2011 using the RGEC method, which includes the following components: Risk profile, Good Corporate Governance (GCG), Earnings, and Capital. This study aims to determine the condition of commercial banks as either very healthy, healthy, or sufficiently healthy, and to compare the health levels between Government-Owned Commercial Banks and National Private Commercial Banks. The research results indicate that the overall score for NPL, LDR, GCG, ROA, ROE, NIM, BOPO, and CAR ratios from 2017 to 2021 for National Private Commercial Banks is more stable compared to Government-Owned Commercial Banks, which means that the performance of National Private Commercial Banks is better overall. Although Government-Owned Commercial Banks performed better in terms of total score in 2017 and 2018, they experienced a decline in subsequent years. The assessment shows that National Private Commercial Banks perform better or health in terms of profitability and net income. Both types of commercial banks perform equally well in reducing non-performing loans, providing funds to their debtors, and maintaining capital adequacy.